Aktivitas Antioksidan dan Penetapan Kadar Fenol Total Ekstrak Metanol Dedak Bebeapa Varietas padi (Oryza sativa L.) - Sugiat, Dede; Hanani, Endang; Mun’im, Abdul (Majalah Ilmu Kefarmasian, 2010)
Antioxidant has been known to have an important role in the prevention and treatment of diseases. In recent years, many plants have been explored to obtain new antioxidants from natural products. Rice has been known rich in antioxidative compounds. However, there is little attention to the co- or by- products from rice (Oryza sativa) milling plant. One of the products is rice bran. In this study ten varieties of rice bran, which are commonly cultivated varieties in Indonesia were studied their antioxidant activity and total phenolic content. The antioxidant activity was examined by DPPH scavenging assay and total reducing power, while total phenolic content was determined by Folin-Ciocalteu reagent. The results of this study showed that the methanolic extract of IR-64 variety demonstrated the strongest DPPH radical scavenger activity with IC50 350.64 ppm, while in reducing power activity was exhibited by methanolic extract of IR-42 variety. However, the highest total phenolic content (71.85 mg gallic acid equivalent/gram) was found in methanolic extract of OM-4495 rice bran. These result indicated that the methanolic extract of rice bran might potentially be natural antioxidants.